Tissue Factor Expression and Metastatic Potential of Colorectal Cancer - Shigemori, Chika; Wada, Hideo; Matsumoto, Kouichi; Shiku, Hiroshi; Nakamura, Shin; Suzuki, Hiroshi (Thrombosis and Haemostasis, 1998)
Several studies have previously demonstrated tissue factor (TF) expression in solid tumors. In our study, we evaluated by immunohistochemical staining TF expression in 79 cases of colorectal cancer and 17 cases of metastatic cancer of the liver from colorectal cancer, and investigated the relationship between the clinicopathological features and TF expression.TF was detected in the tumor of 57% of colorectal cancer patients, and its expression was significantly increased (p = 0.01) in metastatic tumors (88%). TF expression was more commonly observed in meta-static tumors than in any Dukes’ stage of primary cancer. In primary cancer, the detection of TF was more frequent in cases with lymph node metastasis (Dukes’ C, 63%) or with hematogenous metastasis (Dukes’ D, 82%) than in tumors without lymph node or hematogenous metastasis (Dukes’ A and B, 46%, p = 0.03).These results suggest that the expression of TF is related with the metastatic potential of colorectal cancer.